Call for global standards in clinical yoga trials - Atul Kumar Goyal (Wolters Kluwer Medknow Publications, 2019)
Clinical yoga trials, which were conducted in medical research institutes, found to skew toward imposing positive health impacts. Several concerns related with the clinical yoga trials including the availability of exclusive ethical committee to review yoga research proposal, compensation to the poor patients, patient's actual will to participate in the study, yoga trainer qualification, insurance policy for patients if being harmed, standard yoga protocols (exercise, stretching, bending, meditation, music, timings, and duration), mode of training (self-practice by video or personal trainer), assessment of level of compliance, religious concerns, law and legislation have been neglected, not highlighted, or not well justified by most of the studies. The present article represents the grassroot level of experience of clinical yoga trials in medical research institutes and recommended that, until and unless the global standards for clinical yoga trials have not been introduced, for the safety of the patient, either yoga trials should not be allowed in medical and research institutes or all institutions should follow the standard study designs described in highly indexed standard journals.